Production of polyacrylonitrile nanofibres modified with Cyanex 272 for recovery of gallium from solution - Segala, Bibiane N (Environmental technology, 2022)
The objectives of this work were to develop polyacrylonitrile nanofibres modified with the commercial Cyanex 272 extractor and apply them for the recovery of gallium present in aqueous solution. The nanofibres were produced using the centrifugation technique, employing Forcespinning® equipment. The average nanofibre diameter ranged from 530 to 840 nm. The highest adsorption of gallium was achieved at pH 2.5, with a pseudo-second order kinetic model and the Freundlich equilibrium isotherm model providing the best fits of the experimental data. The thermodynamic parameters showed that the adsorption was spontaneous, favourable, and endothermic. The maximum capacity of the PAN/Cyanex 272 nanofibres for the recovery of gallium was 38.93 mg g-1. In successive reuse cycles, the nanofibres showed a small decrease of the adsorption capacity for the metal after the first cycle, while the efficiency remained constant in the subsequent cycles. The desorption efficiency remained constant throughout the cycles, with values in the range 80%-90%. The findings demonstrated that PAN/Cyanex 272 nanofibres have excellent potential for use as adsorbents, providing good capacity for the recovery of gallium and satisfactory stability during reuse in several cycles